Effect of competitive adsorption on the transport of multiple pollutants through a compacted clay liner. Issue 2 (February 2021) - Shu, Shi; Zhu, Wei; Fan, Xihui; Wu, Silin; Li, Yunquan; Ng, Charles Wang Wai
Leachate transport through municipal solid waste (MSW) landfill liners can be slowed considerably by adsorption. MSW landfill leachate contains a large variety of pollutants at very different concentrations, and there will be competitive adsorption as these pollutants are transported through the landfill's compacted clay liner (CCL). In this study, we used batch adsorption tests and geotechnical centrifuge modelling to examine how the adsorption of pollutants commonly found in leachate changed under competitive adsorption conditions and how competitive adsorption affected the CCL breakthrough of multiple pollutants. The results showed that the adsorption of the target pollutant on clay decreased by approximately 30% when competing pollutants were added. The speed at which the pollutants were transported through a 2-m-thick CCL increased, and the breakthrough times reduced by up to 24.8%, when the competing pollutants were mixed. Competitive adsorption significantly promoted the CCL breakthrough of pollutants at low concentrations, but it had limited effect on pollutants at high concentrations.